Reduksi Cacat Sink Mark pada Proses Injection Molding Polioksimetilena (POM) Melalui Pemodelan Termal dan Optimasi Parameter Proses - Topandi, Abdussalam; Khadijah S. Nisa; Herlin Arina; Subhan Rizki Fadilah; Diva Pahlevi Putra Aumee; Pranata (Jurnal Inotera, 2026)
This study aims to minimize sink-mark defects in polyoxymethylene (POM) injection-moulded products through thermal modelling and process parameter optimization. The end-of-packing temperature (TEOP) was estimated using a one-dimensional transient cooling model. At the same time, the specific volume at the end of packing (vEOP) was calculated using the Two-Domain Tait Equation of State. Volumetric (SV) and linear shrinkage (SL) were derived following Chen’s shrinkage framework. Results showed that vEOP ranged from 0.1640 to 0.1764 m³/kg, SV ranged from 13.30 to 19.40%, and SL ranged from 4.64 to 6.94%. Higher TEOP correlated with increased vEOP and higher shrinkage, indicating ineffective packing. Optimization revealed that a melt temperature of 203.41 °C, combined with TEOP of 145.02 °C and a cooling temperature of 16 °C, produced zero shrinkage in the model. These findings provide a quantitative basis for defining process control limits for melt temperature, coolant stability, and packing conditions to reduce sink marks and improve dimensional consistency of POM products.